Penerapan Aplikasi Web Upload Download menggunakan PHP pada Laboatorium Komputer LP3I Tasilmalaya - Usep Abdul Rosid (Jurnal Sistem Informasi Galuh, 2023)
The web application is an application that can accessed using either a web browser via internet or intranet network. The web application gives it easy for user to access data on the server computer. Especially in access data with uploading or downloading files. Easy in accessing data using web applications, especially uploading and downloading files is expeted by an institution or agency. As in LP3I Tasikmalaya, especially in the computer laboratories. The upload download web application is different with sharing files on the computer default. Upload download web application implemented using the intranet and PHP programming language can help LP3I Tasikmalaya especially in the computer laboratories that became another way to access data from a server computer to client computer or otherwise.